Status of the members of election commissions: legislation, practice and international experience - Yerzhanova, F.A.; Mussіlіmovа, K.S. (Ye.A.Buketov Karaganda State University Publishing house, 2019)
In the article topical issues of legal status of electoral bodies of the Republic of Kazakhstan and their members are considered on the basis of studying and analyzing the current legislation of the Republic of Kazakhstan and foreign countries, scientific literature in the field of electoral law and the electoral process, the law enforcement practice of electoral campaigns. The central place is given to the study of the Constitutional Law of the Republic of Kazakhstan «On elections in the Republic of Kazakhstan» which enshrines the rights, duties, restrictions and liability of members of election commissions. A legal analysis of the changes and additions made to the Constitutional Law of the Republic of Kazakhstan «On elections in the Republic of Kazakhstan» is given, the purpose of which was to increase the professionalism of members of election commissions. The necessity of further development of the election legislation is established, proposals on amendments to the normative legal acts determining the status of members of election commissions are formulated. In the article foreign experience in regulating the status of electoral bodies with the aim of the possible use of certain provisions in the current legislation of the Republic of Kazakhstan is discussed. The main aims and the first improvement of the legal status of electoral bodies and their members are defined: increasement of the level of professionalism and independency of electoral commissions; ensurement of equal representation in the commissions of political parties; guaranteeing of transparency and accountability in the work of election commissions.
Сайлау комиссиясы мүшелерінің мəртебесі: заңнама, тəжірибе жəне халықаралық тəжірибе
Статус членов избирательных комиссий: законодательство, практика и зарубежный опыт
Keywords: Constitutional law of the Republic of Kazakhstan «On elections in the Republic of Kazakhstan»; election commissions; member of election commission